Channel Confinement of Aromatic Petrochemicals via Aryl–Perfluoroaryl Interactions With a B←N Host - Campillo-Alvarado, Gonzalo; D'mello, Megan M.; Sinnwell, Michael A.; Höpfl, Herbert; Morales-Rojas, Hugo; MacGillivray, Leonard R. (Frontiers in Chemistry, 2019)
We report channel confinement properties of an electron-deficient boron host derived from the orthogonal B←N interaction between a boronic ester and trans-pentafluorostilbazole. The boron host forms one-dimensional channels in the crystalline solid state when crystallized with common electron-rich aromatic petrochemicals (i.e., benzene, toluene, o-xylene) to form solvates and a cocrystal with stilbene. Molecular confinement of the electron-rich molecules in the solids is achieved through a combination of aryl–perfluroaryl interactions (π–πF) and hydrogen bonds.